EVALUASI ATAS PENYELESAIAN KEBERATAN DALAM UPAYA MENYELESAIKAN SENGKETA DI BIDANG PERPAJAKAN (Studi Kasus Pada Kantor Wilayah DJP Jawa Timur III) - Putra, Haris Darmawan (Jurnal Mahasiswa Perpajakan, 2014)
This research based on the objection from the Taxpayer because of there is differences opinion, misperception of regulation, the dereliction of Taxpayer and the length of time the issuance of the Â Objection Decision Letter. Based on the research, it can give briefly understanding that the objection of tax cases which had done by Directorate General of Taxation East Java III is properly correct with the procedure. Reviewers Objection must investigate formal requirement before then doing investigate based on material requirements such as calling Taxpayer, borrowing books, note, data, and information owned by Taxpayer that related to the content of dispute. Not only that but also Reviewers Objection must invite Taxpayer to get acceptance whether Taxpayer will accept or not from the research that conducted by Reviewers Objection before giving decision for twelve (12) month. From the conclusion, that should be evaluated is to anticipate the new Reviewers Objection that previously had ever served as Reviewers Objection that requires more time when complete a case of objections tax and need increasing for Reviewers Objection quantity. Keyword: Taxpayer, Objection Decision Letter, Reviewers Objection.